(untitled) (Research, Society and Development, 2022)
Ora-pro-nobis has its center of origin in tropical America. It is found in Brazil, from the Northeast to Rio Grande do Sul. The plant belongs to the Cactaceae family, Pereskia genus. Its leaves and fruits contain bioactive compounds that may have expectorant properties and can be used to alleviate inflammatory processes in traditional medicine. Despite its richness, the plant is still little used by the general population and the food and pharmaceutical industries. Some extraction methods are used to obtain bioactive compounds from crude plant extracts, such as maceration, supercritical fluid, and ultrasound-assisted extraction, which have stood out for meeting the principles of green chemistry. The chemical characterization of the extracts obtained through chromatographic analysis by GC-MS/MS and LC-MS/MS proves to be extremely effective, as it allows quantifying the various chemical species present in the extract, making it possible to evaluate and compare the results generated in each chosen extraction condition. The objective of this research is to conduct a review study about the Pereskia aculeata Miller plant. To this end, an exploratory study was carried out, by means of theoretical surveys through Science direct, Capes, Scielo and Pubmed databases. Extracting from plants using different methods is an important step for the industry, ensuring improvement in the quality of products, especially in the food and pharmaceutical sectors. In this sense, no comparative study was found in the literature employing different extraction methods for ora-pro-nobis in the sense of identifying the best method, one with better yield and greater amount of bioactive compounds. The search for different extraction strategies integrated with processes and products that can extract intelligently, minimizing waste, shows an innovative potential in future research.